Lithospheric structuration onshore-offshore of the Sergipe-Alagoas passive margin, NE Brazil, based on wide-angle seismic data. (December 2018) - ,; Morvan, L.; Mazé, J.P.; Pierre, D.; Roudaut-Pitel, M.; Rio, I.; Alves, D.; Barros Junior, P.; Biari, Y.; Corela, C.; Crozon, J.; Duarte, J.L.; et al.
Abstract: The structure and nature of the crust underlying the Camamu-Almada-Jequitinhonha-Sergipe-Alagoas basins System, in the NE Brazilian margin, were investigated based on the interpretation of 12 wide-angle seismic profiles acquired during the SALSA (Sergipe ALagoas Seismic Acquisition) experiment in 2014. In this work, we present two 220-km-long NW-SE combined wide-angle and reflection seismic profiles, SL 01 and SL 02, that have been acquired using 15 ocean-bottom-seismometers along each profile, offshore the southern part of the Sergipe Alagoas Basin (SAB), north of the Vaza-Barris Transfer zone. The SL 02 has a 150-km long inland continuation with 20 land-seismic-stations until the Sergipano Fold Belt (SFB). Wide-angle seismic forward modeling allows us to precisely divide the crust in three domains: beneath the continental shelf, a ∼100 km wide necking zone is imaged where the continental crust thins from ∼35 km on the Unthinned Continental Domain, which displays a three-layered crust structure, to less than 8 km on the Oceanic Crust Domain. In the necking zone, the upper and the middle layers thin dramatically and almost disappear, while the Moho discontinuity shows clear PmPs. The Continental-Oceanic Crust Boundary (COB) is located at ∼80 km from the coastline and is marked by intracrustal seismic reflectors and changes in the seismic velocity, showing a sharp transition. On profile SL02, the oceanic crust is perturbed by a volcanic edifice together with an anomalous velocity zone underneath the area. Highlights: Sergipe Alagoas Basin passive margin modeling. Wide-angle refraction seismic integrated with Multi-Channel reflection seismic data. Location of the Continental- Oceanic crust boundary. Lithospheric structuration and segmentation of Brazil's margin in Central Atlantic.